Analysis of Family Health with a Combination of Naive Bayes KNN Methods - Ona Maliki; Muis Nanja (STMIK Pringsewu, 2023)
Health is a very important part in the life of our nation and country, in a developed and developing nation there is a healthy society. Healthy can be defined as the state of an individual who is prosperous both physically, economically and socially. Health is what needs to be maintained and cared for for the survival of a nation and state. Seeing the importance of the health element in a nation, the government has implemented the Nawacita program with one of the points referring to family health. In implementing the healthy family program, the government has sought to collect data and control healthy families with a family approach. Looking at the data collection system for healthy families with status determination, that is, averaging the indicator values to get the family's health status. The researcher intends to develop in terms of determining family health status by using a combination method of the K-Nearest Neighbor (KNN) method with Naïve Bayes with the aim of knowing the results of applying the method and obtaining better results. Based on the results of the research conducted, the accuracy value of 93.53% was obtained in the combination model of the Naïve Bayes KNN method. So it can be concluded that the combination of these methods is good for determining family health status.